Beyond Grammar Correction: Targeted Micro-Revision as a Scaffold for EFL Academic Writing Development - Ismail, Ismail; Jabri, Umiyati (Majesty Journal, 2026)
Background. Revision is a crucial component of academic writing; however, many EFL students still experience difficulties revising their drafts beyond surface-level grammar correction. In higher education contexts, students need explicit and manageable instructional support to revise paragraph organization, coherence, evidence, sentence clarity, and academic word choice. Purpose. This study aimed to examine the implementation of targeted micro-revision exercises and explore their contribution to students’ writing revision skills in an Academic Writing course. Methods. This study employed a classroom-based qualitative case study supported by descriptive analysis of students’ writing drafts. The participants were 22 fourth-semester students in the English Education Study Program at Universitas Muhammadiyah Enrekang. Data were collected through students’ initial and revised drafts, classroom observation notes, targeted micro-revision checklists, pinpoint peer review sheets, and student reflection questionnaires. The data were analyzed using descriptive and thematic procedures. Results. The findings showed that targeted micro-revision exercises were implemented through orientation, a specific revision focus, lecturer modelling, guided practice, individual revision, peer review, checklist use, feedback, and reflection. Students’ writing improved across ten assessed aspects, with the mean total score increasing from 20.95 in the initial drafts to 30.73 in the revised drafts. Students also responded positively to the exercises, particularly to lecturer modelling, checklist use, and gradual revision. Conclusion. Targeted micro-revision exercises can function as a practical scaffold for developing EFL students’ academic writing revision skills, although continued support is needed in grammar, evidence explanation, and coherence development.